Evaluation of Serum GPX4 Levels and rs713041 Polymorphism in Hypertensive Patients: A Case-Control Study in Dhi Qar Province, Iraq - Ghulam, Zahraa Suwaih; Ahmed, Intisar Hussein (American Journal of Biology and Natural Sciences, 2025)
Hypertension is a prevalent cardiovascular condition associated with increased oxidative stress. Glutathione Peroxidase 4 (GPX4) is a critical antioxidant enzyme that protects cells from oxidative damage. This case-control study aimed to assess serum GPX4 levels and the rs713041 T/C polymorphism of the GPX4 gene in hypertensive patients compared to healthy controls in Dhi Qar Province, Iraq. Our findings indicate significantly lower serum GPX4 levels in hypertensive patients, suggesting compromised antioxidant defense mechanisms.